The Southeast Missouri (USA) Proterozoic iron metallogenic province—types of deposits and genetic relationships to magnetite–apatite and iron oxide–copper–gold deposits - Nold, JL; Dudley, MA; Paul Davidson (2014)
The Southeast Missouri (USA) iron metallogenic province within the Mesoproterozoic St. Francois Mountains terrane includes eight major iron deposits and approximately 30 minor deposits. Three of the major deposits have been mined: Pilot Knob magnetite, Iron Mountain, and Pea Ridge. These deposits have similarities to “Kiruna-type” iron deposits, and likely formed either by crystallization of iron oxide magma, and/or by hydrothermal replacement of volcanic rocks. Iron oxides within all district deposits are dominantly magnetite and hematite, but the gangue minerals are diverse. At Pilot Knob magnetite the dominant gangue mineral assemblages are albitic plagioclase–K-feldspar–quartz–chlorite; at Iron Mountain, andradite–actinolite–apatite–quartz; and at Pea Ridge, apatite–quartz in the main part of the deposit, plus REE-bearing breccia pipes, discussed below. Pilot Knob magnetite and Pea Ridge have associated carbonates which have been suggested to indicate carbonatitic affinities for these deposits. The Boss–Bixby deposit has been described as an iron oxide–copper–gold (IOCG) deposit, and contains the only significant copper resource known in the district (~40 Mt of 0.8% Cu), as yet undeveloped. The district also has steeply dipping iron oxide vein deposits that represent part of the plumbing system where iron-bearing hydrothermal fluids moved upward towards the surface from the iron orebodies developing at depth. Some of these hydrothermal fluids were exhaled into caldera lakes and formed small deposits composed of laminated, oolitic sedimentary hematite.